Insights from a pan India Sero-epidemiological survey (Phenome-India Cohort) for SARS-CoV2 - Naushin, Salwa; Sardana, Viren; Ujjainiya, Rajat; Bhatheja, Nitin; Kutum, Rintu; Bhaskar, Akash Kumar; Pradhan, Shalini; Prakash, Satyartha; Khan, Raju; Rawat, Birendra Singh; Tallapaka, Karthik Bharadwaj; Anumalla, Mahesh; et al. (eLife, 2021)
To understand the spread of SARS-CoV2, in August and September 2020, the Council of Scientific and Industrial Research (India) conducted a serosurvey across its constituent laboratories and centers across India. Of 10,427 volunteers, 1058 (10.14%) tested positive for SARS-CoV2 anti-nucleocapsid (anti-NC) antibodies, 95% of which had surrogate neutralization activity. Three-fourth of these recalled no symptoms. Repeat serology tests at 3 (n = 607) and 6 (n = 175) months showed stable anti-NC antibodies but declining neutralization activity. Local seropositivity was higher in densely populated cities and was inversely correlated with a 30-day change in regional test positivity rates (TPRs). Regional seropositivity above 10% was associated with declining TPR. Personal factors associated with higher odds of seropositivity were high-exposure work (odds ratio, 95% confidence interval, p value: 2.23, 1.92-2.59, <0.0001), use of public transport (1.79, 1.43-2.24, <0.0001), not smoking (1.52, 1.16-1.99, 0.0257), non-vegetarian diet (1.67, 1.41-1.99, <0.0001), and B blood group (1.36, 1.15-1.61, 0.001).

Case report: a fatal case of babesiosis in a splenectomized male patient from Western India - Godbole, Ravi; Gaur, Avantika; Nayar, Priyanka; Kiruthiga, Kala; D'Costa, Pradeep; Manchanda, Rumma; Khilari, Ajinkya; Shanmugam, Dhanasekaran; Muglikar, Kalpana D.; Kundu, Krishnendu (American Journal of Tropical Medicine and Hygiene, 2022)
Human babesiosis is a rare disease, caused by Babesia species and commonly transmitted by tick bite. Although human babesiosis is known to be asymptomatic in immunocompetent hosts, clinical cases of severe babesiosis have been reported from splenectomized or immunocompromised individuals. To our knowledge, only one case of human babesiosis in India has been previously reported. Here, we report a case of severe babesiosis with high parasitemia (similar to 70%) in a 30-year-old asplenic farmer. The patient presented with fever, yellowish discoloration of skin, oliguria, and anemia; he eventually developed multiorgan failure syndrome and died. Peripheral blood films were prepared and used to confirm the presence of piroplasms by microscopy. Total DNA isolated from blood was used for 18S ribosomal RNA gene fragment amplification by polymerase chain reaction, which was subjected to Sanger sequencing. Although 18S sequence indicated that the Babesia species infecting the patient was similar to that of other Babesia species originating from wild mammals, species identification could not be done. Phylogenetic analysis revealed that the patientderived pathogen is distinct because it forms a separate clade in the cladogram.

Tale of two waves: Delineating diverse genomic and transmission landscapes driving the COVID-19 pandemic in Pune, India - Niveditha, Divya; Khan, Soumen; Khilari, Ajinkya; Nadkarni, Sanica; Bhalerao, Unnati; Kadam, Pradnya; Yadav, Ritu; Kanekar, Jugal B.; Shah, Nikita; Likhitkar, Bhagyashree; Sawant, Rutuja; Thakur, Shikha; et al. (Journal of Infection and Public Health, 2023)
Background: Modern response to pandemics, critical for effective public health measures, is shaped by the availability and integration of diverse epidemiological outbreak data. Tracking variants of concern (VOC) is integral to understanding the evolution of SARS-CoV-2 in space and time, both at the local level and global context. This potentially generates actionable information when integrated with epidemiological outbreak data.Methods: A city-wide network of researchers, clinicians, and pathology diagnostic laboratories was formed for genome surveillance of COVID-19 in Pune, India. The genomic landscapes of 10,496 sequenced samples of SARS-CoV-2 driving peaks of infection in Pune between December-2020 to March-2022, were determined. As a modern response to the pandemic, a ``band of five'' outbreak data analytics approach was used. This integrated the genomic data (Band 1) of the virus through molecular phylogenetics with key outbreak data including sample collection dates and case numbers (Band 2), demographics like age and gender (Band 3-4), and geospatial mapping (Band 5).Results: The transmission dynamics of VOCs in 10,496 sequenced samples identified B.1.617.2 (Delta) and BA(x) (Omicron formerly known as B.1.1.529) variants as drivers of the second and third peaks of infection in Pune. Spike Protein mutational profiling during pre and post-Omicron VOCs indicated differential rank ordering of high-frequency mutations in specific domains that increased the charge and binding properties of the protein. Time-resolved phylogenetic analysis of Omicron sub-lineages identified a highly divergent BA.1 from Pune in addition to recombinant X lineages, XZ, XQ, and XM. Conclusions: The band of five outbreak data analytics approach, which integrates five different types of data, highlights the importance of a strong surveillance system with high-quality meta-data for understanding the spatiotemporal evolution of the SARS-CoV-2 genome in Pune. These findings have important implica-tions for pandemic preparedness and could be critical tools for understanding and responding to future outbreaks.& COPY; 2023 Published by Elsevier Ltd on behalf of King Saud Bin Abdulaziz University for Health Sciences. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: COVID-19; Delta; Omicron; SARS-CoV-2 genomic surveillance; Variant of concern; Whole Genome Sequencing (WGS)

Dietary supplementation of lactococcus lactis subsp. lactis BIONCL17752 on growth performance, and gut microbiota of broiler chickens - Navale, Vishwambar D.; Yadav, Rakeshkumar; Khilari, Ajinkya; Dharne, Mahesh; Shanmugam, Dhanasekaran; Vamkudoth, Koteswara Rao (Probiotics and Antimicrobial Proteins, 2024)
The rapid rise of antimicrobial resistance (AMR) is a global concern, being triggered by the overuse or misuse of antibiotics in poultry farming sector. We evaluated Lactococcus lactis subsp. lactis BIONCL17752 strain, and characterized its probiotic potential to endure hostile gastrointestinal conditions. Genome sequencing analysis revealed probiotics traits, and gene clusters involved in bacteriocins, lactococcin A, and sactipeptides production. The absence of genes for antibiotic resistance, virulence, and biogenic amine production indicates the potential of probiotic strain. The BIONCL17752 strain was explored for antibiotic-free feed supplement for growth promotor in broiler chicken. The feed supplemented with 4 x 109 CFU/kg of probiotic strain, in combination with various concentrations of fructooligosaccharides (FOS) 1.0, 2.5, and 5.0 kg/tonne in starter, grower, and finisher diets, respectively. A significant improvement of body weight 152 to 171 g/bird (p < 0.05), and a low feed conversion ratio (FCR) of 1.62, was achieved without using synthetic antibiotics for growth promotion. The results of biochemical, hematological, and histological examinations showed normal features, indicating that the treatment had no harmful effects on the bird's health. Reduced levels of cholesterol, triglycerides, high-density lipoprotein (HDL), and low-density lipoprotein (LDL) in serum are an indication of the health benefits for the treated birds. Microbial community analysis of fecal samples of poultry birds exhibited a higher abundance of Bacteroidetes, Firmicutes, Proteobacteria, Actinobacteria, and Fusobacteria. Probiotic treatment resulted in reduced Firmicutes and increased Bacteroidetes (F/B ratio) in the broiler's gut which highlights the benefits of probiotic dietary supplements. Importantly, the probiotic-fed group exhibited a high abundance of carbohydrate-active enzymes (CAZyme) such as glycoside hydrolases (GH), glycoside transferases (GT), and carbohydrate-binding module (CBM) hydrolases which are essential for the degradation of complex sugar molecules. The probiotic potential of the BIONCL17752 strain contributes to broilers' health by positively affecting intestinal microbiota, achieving optimal growth, and lowering mortality, demonstrating the economic benefits of probiotic treatment in organic poultry farming.
Keywords: Antibiotic growth promotor; Broiler chickens; Functional genome analysis; Growth performance; Gut microbiota; Lactococcus lactis subsp. lactis

32nd National Congress of Parasitology, Pune: bringing together India's parasitologists - Purkayastha, Devatrisha; Pandit, Kushankur; Upadrasta, Sindhuri; Khilari, Ajinkya; Shanmugam, Dhanasekaran; Karmodiya, Krishanpal (Trends in Parasitology, 2025)
The 32nd National Congress of Parasitology (NCP) was held in person, 3-5 October 2024, at the Indian Institute of Science Education and Research Pune (IISER Pune), jointly organized by IISER Pune; the Council of Scientific and Industrial Research - National Chemical Laboratory, Pune; and Savitribai Phule Pune University (formerly University of Pune) in association with the Indian Society for Parasitology. The conference brought together around 250 attendees from across the country and abroad, including a diverse group of researchers, clinicians, industry experts, and students. The event provided a collaborative environment for exchanging research ideas relevant to the field of parasitology. The congress emphasized the concept of One Health, a holistic approach to address parasitic infections affecting humans and animals to promote overall health and well-being. In this TrendsTalk, the organizers provide an overview of the conference proceedings, which brought together India's vast and diverse parasitology community.

Detection and variant characterization of lumpy skin disease virus from dairy cattle in India - Bajpai, Manali; Khilari, Ajinkya; Likhitkar, Bhagyashree; Musale, Pankaj; Jadhav, Santoshkumar; Dhanikachalam, Velu; Kakramkar, Payal; Bhave, Kaustubh; Swaminathan, Marimuthu; Joshi, Sachin; Shanmugam, Dhanasekaran (Virus Evolution, 2025)
The spread of a severe and often fatal form of lumpy skin disease (LSD) in cattle and water buffaloes has caused widespread mortality and morbidity of these animals in India. To track and understand the genetic changes occurring in the virus and to enable routine surveillance of the virus, multiplexed polymerase chain reaction (PCR) and sequencing methods were developed and validated in this study. Multiplexed nested PCR for LSD virus (LSDV) detection was optimized using skin lesion swabs and nasal samples collected from symptomatic and asymptomatic animals. For genotyping, overlapping PCRs to amplify the entire LSDV genome were developed and tested on field samples collected from the Maharashtra and Odisha states of India. Analysis of LSDV genomes from 41 field samples collected in 2022 and 2023 revealed the presence of highly conserved novel mutations. Phylogenetic analysis shows that a distinct genotype of LSDV has spread across India, which warrants genomic surveillance of the virus in the coming years to track the evolution and transmission of the virus. The non-invasive sample collection, detection, and genotyping methods described in this study can facilitate large-scale surveillance of LSDV in dairy animals.
Keywords: genotyping by sequencing; lumpy skin disease; multiplexed nested PCR; Oxford Nanopore technology; virus surveillance

Identification of genetic variations linked to buparvaquone resistance in Theileria annulata infecting dairy cattle in India - Musale, Pankaj; Khilari, Ajinkya; Gade, Rohini; Dhanikachalam, Velu; Jadhav, Santoshkumar; Bajpai, Manali; Turakani, Bhagya; Joshi, Akshay; Prajapati, Amar; Srivastava, Anand; Swaminathan, Marimuthu; Joshi, Sachin; et al. (Plos One, 2025)
Buparvaquone (BPQ) is used for the treatment of bovine theileriosis, a tickborne disease caused by parasites of the Theileria genus. Studies on T. annulata have linked the mechanism of BPQ resistance predominantly to genetic variations in the parasite cytochrome b (cytb) gene. In addition, cryptic mechanisms of resistance involving the parasite peptidyl-prolyl isomerase (pin1) and dihydroorotate dehydrogenase (dhodh) genes require assessment. In India, where bovine theileriosis is endemic, and BPQ is widely used for treatment, it is necessary to establish the prevalence of genetic variations linked to BPQ resistance. In this study, multiplexed PCR amplification and nanopore sequencing method was used for genotyping the complete gene loci of the three target genes. Analysis of 454 T. annulata field samples collected from seven different states of India revealed the presence of previously reported BPQ resistance associated variations S129G, A146T and P253S in cytb gene and A53P in pin1 gene. The A146T and I203V variations in cytb were found to be prevalent and mostly co-occurring, and their role in BPQ resistance needs further evaluation. This study has revealed the presence of previously reported BPQ resistance-linked mutations in cytb and pin1 genes in T. annulata infecting dairy cattle in India and establishes an Oxford nanopore sequencing method suitable for large-scale surveillance of genetic variation in Theileria parasites from field samples.

Targeted genomic surveillance unveils genetic variations linked to regional malaria drug resistance dynamics in India - Khilari, Ajinkya; Sharma, Shweta; Bajpai, Manali; Viswan, K. Anju; Chaturvedi, Rini; Mirdha, Bijay R.; Rahi, Manju; Sharma, Amit; Shanmugam, Dhanasekaran (Open Forum Infectious Diseases, 2026)
Background India has made substantial progress in reducing Plasmodium falciparum malaria cases and has set a target to eliminate malaria by 2030. Although artemisinin-based combination therapy (ACT) treatment remains effective, tracking regional differences in genetic variants associated with antimalarial resistance is required for effective drug policy implementation.Methods We analyzed 238 P. falciparum clinical samples from 6 Indian states by sequencing 15 parasite genes associated with reduced drug effectiveness. The method involved nanopore sequencing of target gene amplicons derived from dried blood spots using a highly-sensitive PfMDR15 surveillance panel.Results India's historical policy of artesunate-sulfadoxine-pyrimethamine in central India and artemether-lumefantrine in the Northeast has shaped contrasting resistance profiles. In the Northeast, chloroquine resistance persisted at high frequency (Pfcrt K76T and CVIET haplotype; Pfaat1 S258L), alongside quintuple and sextuple Pfdhfr-Pfdhps haplotypes conferring complete sulfadoxine-pyrimethamine resistance. Central India showed variable chloroquine resistance (parasites largely retained wild-type Pfcrt) and emerging lumefantrine tolerance (Pfmdr1 Y184F, Pfaat1 S258L). Interestingly, Delhi (Central India) parasites resembled profiles from the distant Northeast, which borders South East Asia. The detection of Pfaat1 S258L, previously reported only from Africa and associated with reduced lumefantrine susceptibility, suggests convergent evolution under ACT partner-drug pressure. No WHO-validated Pfk13 artemisinin resistance mutations were detected, supporting continued efficacy of ACT.Conclusions India's resistance landscape is fragmented, with signals of expanding lumefantrine tolerance and importation or evolution of globally relevant mutations. These findings highlight the importance of integrating molecular genomic surveillance into malaria control policy to monitor and protect ACT effectiveness and advance malaria elimination. Monitoring of drug resistance associated mutations in P. falciparum parasites is critical for effective drug treatment. We have demonstrated the use of a scalable genomic surveillance protocol for tracking drug resistance linked mutations in parasite genes from clinical isolates in India. The study suggests extensive regional diversity in antimalarial resistance profiles and provides the first hint of possible emergence of lumefantrine tolerance in India.
Keywords: drug resistance; malaria; Oxford nanopore; P. falciparum; pfMDR15